MODEL PENINGKATAN KAPABILITAS MASYARAKAT PENERIMA BANTUAN DANA BERGULIR PROGRAM KOTAKU BKM BAREALLO KELURAHAN RANTEPAKU TORAJA UTARA - Hidryana Pratiwi; Fasiha; Adzan Noor Bakri; Suryanto (Journal Publicuho, 2025)
This study aims to investigate the capability improvement model of the recipient community of revolving fund assistance for the Slum City program, Bareallo Community Empowerment Agency, Rantepaku Village, North Toraja to reduce bad debts in the area. This study uses a qualitative case study research type where the case analyzed is bad debts that occur in the Bareallo Community Empowerment Agency, Rantepaku Village, North Toraja. The results of the study show that the distribution of revolving funds in Rantepaku goes through three main stages, namely membership in the Community Empowerment Group, having a business, and meeting administrative requirements. Payment constraints are triggered by a lack of financial transparency, indiscipline, and inappropriate use of funds. The strategy for handling bad debts is carried out through periodic collections and increasing awareness of payment responsibilities. The community feels the benefits of revolving funds, with easy access to education, health, and infrastructure, as well as guarantees of basic needs such as food, housing, and poverty control through four main programs.